Tool Path Generation and Finite Element Analysis of Single Point Incremental Sheet Forming for Component Geometric Accuracy - Goyal, Ghansham (My University, 2012)
Single point incremental forming is a flexible process for the production of low volume customized sheet metal parts. A final component is obtained by the localized deformation induced by the forming tool. Toolpaths for different axisymmetric shapes have been generated using MATLAB. It is well known that geometrical accuracy is one major problem in single point incremental forming process due to the bending of the sheet. Finite element analyses have been used to study the geometric accuracies and other features in the present work. The output of simulation is given in terms of final geometric profile, thickness distribution to the component, stress, strain and the tool reaction forces. The geometrical discrepancies are determined by comparing the desired geometry with obtained geometry after finite element analysis. Use of top fillet at the major base of component and height compensation to eliminate over travel has been used to quantify the improvements in accuracy. The single pass deformation strategy shows inhomogeneous thickness distribution in the final deformed component due to left out undeformed portion at the central region of the formed component. A two-step deformation strategy (first outer-to-inner followed by inner-to-outer) has been used to achieve a more uniform distribution of thickness in single point incremental forming. The strain history (strain path and strain increment) is analyzed in single pass deformation for three different geometry shapes (pyramid, cone, other axisymmetric shape) and two steps deformation cone. The three components of force are studied throughout the forming process in the single pass and two pass deformation strategy. It was focused on the influence of four process parameters (draw angle, incremental step size, tool diameter and blank thickness) on the forming forces.
M. E. (CAD/CAM and Robotics)
Keywords: Single Point Incremental Forming; Deformation; Finite Element Analysis; Two-step deformation